The Phenomenon of LGBT (Lesbian, Gay, Bisexual, and Transgender) and The Story of the Shodom in Islamic View - Arina Fadhilaatika; M Muthoifin (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
The purpose of this study is to relearning about of the re-emergence of the Shodom story about homosexuals or LGBT (Lesbian, Gay, Bisexual, and Transgender) and how it is from an Islamic perspective. This research method uses a qualitative study, the type of literature review, with a phenomenological approach and content analysis, namely by using legal content analysis in the Koran, written documents, pictures, electronic documents, and mass media. The results of this study indicate that in almost various countries the phenomenon of Shodom activity is rampant, not only abroad but also in Indonesia. This is evident from various sites that have uploaded much news about LGBT cases in various countries, including in Indonesia. Not even a few homosexual activists want this relationship legalized under the pretext of consensual and human rights. In the view of Islam, it has been explained in the Qur'an Surah al-A’raf : 80 and other literature that this homosexual act is a heinous act that is contrary to the nature of nature, religious rules, and human rights, until Allah SWT sends down punishment for the perpetrators. this deed. Both at the time of the prophet Lut A.S and today. And what are the causes and impacts of homosexual behavior.